Tribological performance of self-lubricating polyoxymethylene composite reinforced with chemically treated oil palm empty fruit bunch fibers for bearing application - Muhalim, Damira; Liza, Shahira; Fukuda, Kanao; Mat Tahir, Noor Ayuma; Yaakob, Yazid (Korean Fiber Society, 2025)
Bearings are one of the important tribological components in machinery that exist in many types of materials tailored to their end application. The commonly used bearing materials is polymer due to lightweight, excellent friction and wear resistance and self-lubricating properties which are not offered by other materials. By taking advantage of the abundancy of oil palm empty fruit bunch (OPEFB) fiber in Malaysia, the development of this material act as an innovative approach in utilizing the agricultural waste. Hence, there is a possibility in transforming the naturally existing fiber, OPEFB, into a sustainable reinforcement material in commercially available bearing materials of polyoxymethylene (POM) for tribological purposes. The aim of this research was to formulate a highly reliable tribology OPEFB/POM composite material for unlubricated sliding bearing application. This can be done by modifying the fiber properties through effective chemical treatment in enhancing its compatibility and interfacial bonding with POM matrix. Finally, the tribological performance of OPEFB/POM composite was evaluated using a ball-on-disc tribology tester under varying loads of 10, 20, and 40 N at a constant sliding distance of 2000 m and a sliding speed of 0.209 m/s. The OPEFB/POM composite has successfully shown a great improvement through its consistency result in low coefficient of friction (0.084–0.100) and low specific wear rate (× 10−5 mm3/Nm). The dominant wear mechanisms were found by the stable formation of transfer layer, plastic deformation, and adhesion which has contributed to the enhanced friction and wear behavior of the OPEFB/POM composite.